2014
DOI: 10.1179/1465313313y.0000000091
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between salivary insulin-like growth factor I and quantitative cervical maturational stages of skeletal maturity

Abstract: Salivary IGF-I levels or its secretion rate can be used as an indicator of skeletal growth but longitudinal data are necessary to confirm salivary IGF-I as a marker for skeletal growth prediction and residual mandibular growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 21 publications
5
22
0
Order By: Relevance
“…It has been suggested that salivary cortisol can be used as a surrogate of free serum cortisol thus offering some advantages over measurements of serum cortisol (Estrada & Orlander, ). However, age, gender, developmental stage, body mass index, sampling and assay conditions are all variables which should be taken into account in studies that use salivary cortisol as a marker (Jessop & Turner‐Cobb, ; Nayak, Bhad Patil, & Doshi, ).…”
Section: Saliva Diagnostics In Conditions Related To Hypothalamic‐pitmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that salivary cortisol can be used as a surrogate of free serum cortisol thus offering some advantages over measurements of serum cortisol (Estrada & Orlander, ). However, age, gender, developmental stage, body mass index, sampling and assay conditions are all variables which should be taken into account in studies that use salivary cortisol as a marker (Jessop & Turner‐Cobb, ; Nayak, Bhad Patil, & Doshi, ).…”
Section: Saliva Diagnostics In Conditions Related To Hypothalamic‐pitmentioning
confidence: 99%
“…Salivary proteomics are also utilized to identify skeletal growth markers during childhood. Salivary insulin growth factor (IGF‐1) was found to be a promising indicator of skeletal maturity (Nayak et al., ). In a pilot study by Wetie et al.…”
Section: Salivary Proteomicsmentioning
confidence: 99%
“…The age group in the studies ranged from 6 to 24 years. The noninvasive methods used were saliva [23][24][25][26][27][28][29][30], GCF [31][32][33], and urine [34].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 12 articles, 8 studies [23][24][25][26][27][28][29] employed saliva as their sample. The biomarkers assessed in the eight studies were insulin-like growth factor 1 (IGF1) [23,29], alkaline phosphatase (ALP) [26,27,34], bone-specific alkaline phosphatase (B-ALP) [24,25], vascular endothelial growth factor (VEGF) [29], and dehydroepiandrosterone (DHEA) [30].…”
Section: Salivamentioning
confidence: 99%
“…For example, concentrations of salivary insulin growth factor ( IGF-I ) may vary and serve as an indicator of skeletal growth throughout childhood (71). Nutritional status of the child also affects salivary biomarkers.…”
Section: Salivary “Omics”mentioning
confidence: 99%